Pengaruh Free Cash Flow, Asset Growth dan Kebijakan Hutang Terhadap Kebijakan Dividen dengan Profitabilitas sebagai Variabel Moderating - Rahayu Rahayu; Florie Nurul (Lembaga Penelitian Universitas YARSI, 2024)
This research seeks to ascertain how debt policy, asset growth, and free cash flow affect dividend policy with profitability as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2020 period. Descriptive research is used in this study with a quantitative approach with the data analysis method used is moderated regression analysis with Eviews version 10. All manufacturing companies that were listed on the Indonesia Stock Exchange between 2018 and 2020 make up the research population. Thirty-seven corporate samples made up the sample, which was selected using the purposive sampling method. Thus, the study's findings indicate that free cash flow has a favorable impact on dividend policy, Asset growth has a negative effect on dividend policy, Debt policy has a negative effect on dividend policy, profitability is able to strengthen the effect of free cash flow on dividend policy, profitability is able to strengthen the effect of asset growth on dividend policy, profitability is able to strengthen debt policy towards dividend policy.